2023
DOI: 10.1002/solr.202370062
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light‐Driven Degradation of Trichloroethylene in Aqueous Phase with Vanadium‐Doped TiO2 Photocatalysts

Abstract: Visible Light‐Driven Degradation In article number http://doi.wiley.com/10.1002/solr.202200938, Van Anh Nguyen, Esteban Mejía, and co‐workers describe a series of vanadium‐doped titanium oxide photocatalysts, and their activity on the aqueous degradation of the persistent organic pollutant trichloroethylene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nowadays, many photocatalysts have been used for the development of photocatalytic hydrogen evolution. Among various semiconductor catalysts, such as Ti 3 C 2 , CdS, Cu 2 O, etc., titanium oxide (TiO 2 ) is a typical semiconductor photocatalyst. , On account of its unique properties of low cost, biological inertness, and chemical inertness, TiO 2 has been widely used as a photocatalyst in the fields of solar water splitting and solar cells. , Nevertheless, its intrinsic drawbacks of wide bandgap energy (3.2 eV) and rapid recombination of photoinduced electron–hole pairs retarded the further improvement of TiO 2 in photocatalytic performance. , In the long run, tremendous efforts are being made to effectively enhance the photocatalytic performance of TiO 2 , such as the modulation and change of the crystal structure and morphology, , the doping of metal or nonmetal elements, the construction of heterojunctions, and so forth. For instance, Liu et al reported that the 0D/2D TiO 2 /CoP composite showed exceptionally improved photocatalytic H 2 evolution performance .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, many photocatalysts have been used for the development of photocatalytic hydrogen evolution. Among various semiconductor catalysts, such as Ti 3 C 2 , CdS, Cu 2 O, etc., titanium oxide (TiO 2 ) is a typical semiconductor photocatalyst. , On account of its unique properties of low cost, biological inertness, and chemical inertness, TiO 2 has been widely used as a photocatalyst in the fields of solar water splitting and solar cells. , Nevertheless, its intrinsic drawbacks of wide bandgap energy (3.2 eV) and rapid recombination of photoinduced electron–hole pairs retarded the further improvement of TiO 2 in photocatalytic performance. , In the long run, tremendous efforts are being made to effectively enhance the photocatalytic performance of TiO 2 , such as the modulation and change of the crystal structure and morphology, , the doping of metal or nonmetal elements, the construction of heterojunctions, and so forth. For instance, Liu et al reported that the 0D/2D TiO 2 /CoP composite showed exceptionally improved photocatalytic H 2 evolution performance .…”
Section: Introductionmentioning
confidence: 99%